THE INFLUENCE OF ENTREPRENEURSHIP EDUCATION AND ENTREPRENEURIAL PROMOTION TO INFLUENCE SALES INTENSITY WITH ENTREPRENEURIAL DIGITALIZATION AS AN INTERVENING VARIABLE (STUDY ON STUDENTS OF VOCATIONAL HIGH SCHOOL IN MOJOKERTO CITY) - Azahra, Shofia; Kusdiyanti, Heny; Sumarsono, Hadi (International Education Trend Issues, 2023)
The purpose of this study is to look at the sales intensity of vocational high school students. The focus of this study is to examine the effect of entrepreneurship education and entrepreneurial promotion to influence sales intensity. In this study, entrepreneurial digitalization is placed as a mediator of the relationship between entrepreneurship education, entrepreneurial promotion, and sales intensity. This research uses quantitative research methods with descriptive design. The respondents of this study were students of public high schools in Mojokerto Regency, namely SMK Negeri 1 Pungging, SMK Negeri 1 Sooko, and SMK Negeri 1 Jatirejo who had received entrepreneurship education and already had a business, namely students in grades XI and XII. The sample of this study amounted to 350 students who filled out the survey using Google Forms. The data analysis method used in this research is Structural Equation Modeling-Partial Least Square (SEM-PLS) using Smart PLS software version 3. This study uses 2 PLS calculation models, namely the measurement model (Outer Model) and the Structural Model (Inner Model). The results of this study indicate that entrepreneurship education has a significant positive effect on sales intensity, entrepreneurship promotion has a significant positive effect on sales intensity, entrepreneurship education has a significant positive effect on entrepreneurship digitalization, entrepreneurship promotion has a significant positive effect on entrepreneurship digitalization, and entrepreneurship digitalization significantly mediates entrepreneurship education and entrepreneurship promotion on sales intensity. This study provides evidence for research that is still debated that entrepreneurship education, entrepreneurship promotion, and entrepreneurship digitalization can positively and significantly influence sales intensity. These findings are also a provision for prospective entrepreneurs to understand and apply the knowledge that has been taught in entrepreneurship.